Spatial transcriptomics reveals heterogeneity of histological subtypes between lepidic and acinar lung adenocarcinoma - Linshan Xie; Hui Kong; Jinjie Yu; Mengting Sun; Shaohua Lu; Yong Zhang; Jie Hu; Fang Du; Qiuyu Lian; Hongyi Xin; Jian Zhou; Xiangdong Wang; et al. (Clinical and Translational Medicine, 2024)
Abstract Background Patients who possess various histological subtypes of early‐stage lung adenocarcinoma (LUAD) have considerably diverse prognoses. The simultaneous existence of several histological subtypes reduces the clinical accuracy of the diagnosis and prognosis of early‐stage LUAD due to intratumour intricacy. Methods We included 11 postoperative LUAD patients pathologically confirmed to be stage IA. Single‐cell RNA sequencing (scRNA‐seq) was carried out on matched tumour and normal tissue. Three formalin‐fixed and paraffin‐embedded cases were randomly selected for 10× Genomics Visium analysis, one of which was analysed by digital spatial profiler (DSP). Results Using DSP and 10× Genomics Visium analysis, signature gene profiles for lepidic and acinar histological subtypes were acquired. The percentage of histological subtypes predicted for the patients from samples of 11 LUAD fresh tissues by scRNA‐seq showed a degree of concordance with the clinicopathologic findings assessed by visual examination. DSP proteomics and 10× Genomics Visium transcriptomics analyses revealed that a negative correlation (Spearman correlation analysis: r = –.886; p = .033) between the expression levels of CD8 and the expression trend of programmed cell death 1(PD‐L1) on tumour endothelial cells. The percentage of CD8+ T cells in the acinar region was lower than in the lepidic region. Conclusions These findings illustrate that assessing patient histological subtypes at the single‐cell level is feasible. Additionally, tumour endothelial cells that express PD‐L1 in stage IA LUAD suppress immune‐responsive CD8+ T cells.